Urgensi Check and Balance oleh Mahkamah Konstitusi melalui Judicial Activism dalam Praktik Demokrasi di Indonesia - Abdur Rozaq, Muhammad; Batara, Surya Daniel; Ramdan Jaya, Muhamad (Universitas Ekasakti, 2024)
The mechanism of checks and balances in a democratic system is intended to avoid the use of hegenomic, tyrannical, and centralization of power, as well as provide performance monitoring activities between state institutions. However, the mechanism of checks and balances by the Constitutional Court related to the doctrine of Judicial Activism is faced with the issue of the independence of the Constitutional Court. This study aims to identify and analyze the mechanism of Checksand Balances by the Constitutional Court by applying Judicial Activism in democratic practices in Indonesia. The research is a doctrinal research and applies the statues approach and deductive analysis methods. The results of the study showed that to ensure the fair exercise of each individual as the fundamental basis of democratic values, the law and politics as an inseparable unit so that the court can use its political power to create a new norm provided for a noble purpose based on the doctrine of judicial activism by developing constitutional texts to create a social change so that the fundamental values in the Constitution can be applied progressively according to progressive legal theory. Judicial Activism is related to the judicial power that serves to check and balance. However, the freedom of judges in Indonesia is limited by the Grundnorm of Pancasila, the 1945 Constitution, legislation, public order and morality, government/political system, economic system, culture.